POLA KELAHIRAN RUSA BAWEAN DI PENANGKARAN DAN PERBANDINGANNYA DENGAN KELOMPOK CERVIDAE LAINNYA - Gono Semiadi; Koestoto Subekti (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 1996)
Bawean deer (Axis kuhlii) is endemic to Bawean island with its status under IUCN record as RARE. Information on the calving pattern in nonexistence and there is a need to understand more on their reproduction physiology for conservation purposes. Record on the calving from Bawean Deer and others tropical deer (Cervus timorensis and Cervus unicolor) from Surabaya zoo were compared. The data were obtained from 1989 to 1996 calving time. The result showed that the mean calving date for Bawean deer is July 14th (SE = 8.3 days, n = 130), Timorensis deer being may 25th (SE = 11.0 days, n = 74), and Sambar deer being Juny 16th (SE = 26.2 days, n = 13). The calving time Bawean deer are spread equally between months, whereas Timorensis and Sambar deer tended to have a peak calving time with Timorensis Deer in July. Due to a small of calving record in Sambar deer, no conclusive result can be gathered.